Effect of sodium chloride on gene expression of Streptococcus mutans and zeta potential of demineralized dentin - Ali Akbar Nagavi-alhoseiny; Maryam Torshabi; Morteza Rasoulianboroujeni; Lobat Tayebi; Fahimeh Sadat Tabatabaei (Elsevier, 2019)
Purpose: In this work, the effects of sodium chloride (NaCl) on gene expression of planktonic Streptococcus mutans cells are investigated. Also assessed are the effects of NaCl on zeta potential of sound and demineralized dentin. Methods: The relative level of glucosyltransferase B (gtfB), gtfC and gtfD transcription of S. mutans in the presence of NaCl was evaluated by quantitative polymerase chain reaction (qPCR). The osmolality of varying salt (NaCl) concentrations and their influence on the zeta potential of sound and demineralized dentin was investigated as well. Results: NaCl significantly reduced the expression of gtfB and C genes in planktonic S. mutans; whereas, gtf D gene expression significantly increased in the presence of NaCl (P < 0.05). NaCl at concentrations of 37.5 mg/ml reduced zeta potential of demineralized dentin, while no significant decrease of zeta potential was found when sound dentin was exposed to this concentration. Conclusion: NaCl reduces the expression of some gtfs in S. mutans and increases negative potential charge of demineralized dentin.